ANALISA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI KECAMATAN DI KOTA BOGOR - Isman Kadar (Universitas Pakuan, 2015)
The purpose of this study was to determine the transformational leadership and discipline of work on job satisfaction of employees in the district of East Bogor.The study population was all employees in Bogor subdistrict East by as many as 105 employees and sample as many as 83 employees of people using slovin. The research instrument was a questionnaire. Collected data is processed using correlation analysis technique.The results show that: 1. There is a positive and significant relationship between transformational leadership and job satisfaction with a correlation coefficient (r) between transformational leadership and job satisfaction of 0.658, meaning that value indicates that there is a relationship strong unidirectional linearity. 2. There is a positive relationship between the discipline of working with employee satisfaction being that the correlation coefficient of 0.421.Keywords: Transformational Leadership, Work Discipline and Job Satisfaction